Implementing Human Resource Information System (HRIS) for Efficient Human Resource Management - Eddy Hermawan Hasudungan Panjaitan (GoAcademica Research & Publishing, 2023)
Technological developments cause the need for changes in resource management. This is done so that resource management in a company becomes more efficient and can compete well with competing companies. One step in developing resource management to increase efficiency is implementing the Human Resource Information System (HRIS). This research will be conducted to see how the implementation of HRIS can improve the efficiency of Human Resource Management. This research will be carried out using a descriptive qualitative approach. The data used in this study comes from various research results and previous studies. The results of this study then found that the existence of HRIS has the potential to increase the effectiveness and efficiency of HRM. This is because HRIS can optimize human resource management in the areas of planning, recruitment and selection, development, performance evaluation, and compensation. This increase can help the organization succeed in competing with other organizations.